Future-Ready Educators: Assessing Digital Competence and Teaching Preparedness Among Prospective Teachers in the 21st Century - Ana Maghfiroh; Erlik Widiyani Styati; Aries Fachriza; Khoiriyah Khoiriyah; Wanida Simpol; Rofi Anwar Syaputra; Lathifah Lathifah (Universitas Muhammadiyah Surakarta, 2024)
In the 21st century, it is critical for teachers to possess digital competence. This research aims at: (1) measuring prospective teachers’ digital competence levels and (2) exploring their perceptions about teaching readiness in the 21st century. The participants consisted of 6 male and 29 female prospective teachers. The DigCompEdu self-reflection tool was used in this study, with a focus on 6 competencies—teaching, guidance, collaborative learning, self-regulated learning, assessment strategies, and feedback and planning—in combination with a questionnaire on teaching readiness in the 21st century. Data from close-ended questions were analyzed statistically, while data from open-ended questions were analyzed and coded using the NVivo 12 Plus application. The results showed that 6% of the participants were at level A1, 28% were at level A2, 46% were at level B1, 14% were at level B2, and 6% were at level C1 of digital competence, but no one was at level C2. In terms of teaching readiness in the 21st century, only some participants expressed their readiness to integrate a variety of digital technologies in the classroom. This research provides an overview of educational study programs that might be useful for developing prospective teachers’ digital competence in the effort to prepare skillful teachers in the 21st century.